2012
DOI: 10.1111/j.1741-2358.2011.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Unnoticed swallowing of a unilateral removable partial denture

Abstract: doi: 10.1111/j.1741‐2358.2011.00621.x Unnoticed swallowing of a unilateral removable partial denture Objective:  This paper presents a case report about an unnoticed swallowing of a partial denture impacted in the esophagus in a 74‐year old man without serious complications. Background data:  Dental prostheses (removable/fixed dental prostheses or fragments of dentures) appear to constitute a significant proportion of swallowed of impacted foreign bodies in the orolaryngopharynx. Conclusion:  This case emphazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Distal attachments were used in 25 patients during endoscopic removal in this study [ 23 , 24 ]. Dentures with clasps or interproximal extensions may cause injury, especially in a narrow segment [ 25 ]. When the end of the sharp part points toward the proximal side, the risk of injury during the retrieval procedure is increased.…”
Section: Discussionmentioning
confidence: 99%
“…Distal attachments were used in 25 patients during endoscopic removal in this study [ 23 , 24 ]. Dentures with clasps or interproximal extensions may cause injury, especially in a narrow segment [ 25 ]. When the end of the sharp part points toward the proximal side, the risk of injury during the retrieval procedure is increased.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have documented such problems with small unilateral RPDs. [1][2][3] In this case an uneventful passage of the denture occurred but more serious complications such as bowel perforation have been documented. Management of such problems usually requires involvement of the MDT within hospital.…”
Section: Swallowed Partial Denturementioning
confidence: 70%
“…Several case reports showed that small unilateral dentures can induce swallowing and aspirating 2,37) . Sufficient retention is needed to avoid swallowing or aspiration of the unilateral RPD.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients may suffer from surgical stress, long treatment period and high cost, and the outcomes of bone augmentation are not always satisfactory 8) . In addition, vertical augmentation is technique sensitive and there may be Yoshiyuki Wada * Harunori Yoshimura Itaru Mikami CLINICAL REPORTS 37 1 2 2017 CLINICAL REPORTS some complications 6,9) . As a result, when the bone volume is poor, implant treatment is often abandoned and the patient has to use RPDs.…”
Section: Introductionmentioning
confidence: 99%